Implementing quotas in university admissions: An experimental analysis - Sebastian Braun; Nadja Dwenger; Dorothea Kübler; Alexander Westkamp (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Quotas for special groups of students often apply in school or university admission procedures. This paper studies the performance of two mechanisms to implement such quotas in a lab experiment. The first mechanism is a simplified version of the mechanism currently employed by the German central clearinghouse for university admissions, which first allocates seats in the quota for top-grade students before allocating all other seats among remaining applicants. The second is a modified version of the student-proposing deferred acceptance (SDA) algorithm, which simultaneously allocates seats in all quotas. Our main result is that the current procedure, designed to give top-grade students an advantage, actually harms them, as students often fail to grasp the strategic issues involved. The modified SDA algorithm significantly improves the matching for top-grade students and could thus be a valuable tool for redesigning university admissions in Germany.
Keywords: C78; C92; D78; I20; 330; college admissions; experiment; quotas; matching; Gale-Shapley mechanism; Boston mechanism; Hochschule; Studienfach; Angebot; Quotenregulierung; Studierende; Nachfrage; Matching; Shapley-Wert; Deutschland